2020
DOI: 10.1002/ecy.3013
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of crustacean zooplankton in transferring allochthonous carbon in a boreal lake

Abstract: v€ ag 4-6, Ume a 90736 Sweden Citation: Grosbois, G., D. Vachon, P.A. del Giorgio, and M. Rautio. 2020. Efficiency of crustacean zooplankton in transferring allochthonous carbon in a boreal lake. Ecology 101(6):Abstract. Increased incorporation of terrestrial organic matter (t-OM) into consumer biomass (allochthony) is believed to reduce growth capacity. In this study, we examined the relationship between crustacean zooplankton allochthony and production in a boreal lake that displays strong seasonal variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
2
13
0
Order By: Relevance
“…Annual production largely depends on inorganic nutrient supply in the summer, but in ice-covered lakes, organic matter produced in the summer is required to sustain biological activity during winter (Lizotte, 2009;Hampton et al, 2017;Teufel et al, 2017;de Melo et al, 2019). Dissolved organic matter (DOM) is processed by the winter bacteria that support heterotrophic flagellates, dinoflagellates, and ciliates (Lizotte, 2009;Vigneron et al, 2019), which are food for small zooplankton and which maintain resident fish populations (Grosbois et al, 2020), ensuring a healthy ecosystem.…”
Section: General Microbial Diversitymentioning
confidence: 99%
“…Annual production largely depends on inorganic nutrient supply in the summer, but in ice-covered lakes, organic matter produced in the summer is required to sustain biological activity during winter (Lizotte, 2009;Hampton et al, 2017;Teufel et al, 2017;de Melo et al, 2019). Dissolved organic matter (DOM) is processed by the winter bacteria that support heterotrophic flagellates, dinoflagellates, and ciliates (Lizotte, 2009;Vigneron et al, 2019), which are food for small zooplankton and which maintain resident fish populations (Grosbois et al, 2020), ensuring a healthy ecosystem.…”
Section: General Microbial Diversitymentioning
confidence: 99%
“…Although boreal lakes and reservoirs differ in many respects, including age, residence time, mean water temperature, and the origin and quality of the OM available (Kalff, 2002;Tadonléké et al, 2012), carbocentric science teaches us that planktonic food webs in northern temperate and boreal lakes as well as in reservoirs are subsidized by allochthonous OM in a large proportion (Del Giorgio et al, 1999;Cole et al, 2002;Cole et al, 2006;Tadonléké et al, 2012;Emery et al, 2015;Grosbois et al, 2020). In fact, terrestrial soils typically provide very active loci for the decomposition of OM, which is exported to and through aquatic systems (Cole et al, 2007).…”
Section: Mehg and Organic Matter A Parallel Fate In Lakes And Reservoirsmentioning
confidence: 99%
“…Autochthonous labile (easily degradable) OM (phytoplanktonderived organic compounds), although present in smaller quantities, has been shown to enhance overall bacterial activity and thus promote the incorporation of flooded allochthonous OM, which is less labile, at the bacterial level (Guillemette et al, 2015) or at a higher level in the trophic chain. In fact, Grosbois et al (2020) recently demonstrated that the efficiency of zooplankton in a boreal lake in transferring autochthonous and allochthonous carbon is equivalent, suggesting that the breakdown of terrestrial detritus and recalcitrant dissolved high-molecular-weight humic substances may be facilitated by co-metabolism using carbon of algal origin (labile autochthonous carbon). The Hg-centric science led to the same findings: the bioavailability of labile carbon in newly flooded areas or in productive lakes promotes bacterial activity (and, in some cases, in deep or warm temperate/tropical waters, anoxia), which, in turn, results in increased mercury methylation rates in the water column and in sediments, and an increase in its final byproduct, MeHg (Mailman et al, 2006;Bo et al, 2016;Bravo et al, 2017;Figures 1A-C).…”
Section: Mehg and Organic Matter A Parallel Fate In Lakes And Reservoirsmentioning
confidence: 99%
“…Long-term metabolism patterns are more indicative of site-specific patterns than are day-to-day variations (Bernhardt et al 2018), but the study length varied among lakes and often focused on summer measurements. Annual trends in metabolism would be interesting to explore, particularly in conjunction with allochthony (Grosbois et al 2020).…”
Section: Remaining Uncertainties and Future Outlooksmentioning
confidence: 99%